UNA RIVER ESTUARY: ECOLOGICAL AND SOCIOECONOMIC ASPECT - Antonio Levino de Carvalho, Marco (Revista Gênero e Interdisciplinaridade, 2023)
This article reports experiences of the elective course “ESTUÁRIO DO RIO UNA: ECOLOGICAL AND SOCIALECONOMIC ASPECT”, proposed by ETE CENTRAL BARREIROS, of the medium course, developed in the community of Abreu do Una, carried out in theperiod from February 18 to July 8, 2022, with informal conversation with residents, community teachers and elementary school students, of both sexes, where topics with some characteristics and curiosities of the Mangrove ecosystem and its components such as fauna and flora were addressed; with the aim of knowing and informing the economicandsocio-environmental importance of the mangroves, encouraging preservation, raising awareness of the benefits to maritime and human life, also promoting a reflection on the current state of conservation of the mangroves in the locality inquestion. The results of this study were: seminars, oral presentation with banner and making models.